2008
DOI: 10.5539/elt.v1n1p29
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Progression Analysis in Teaching Explanation Writing

Abstract: Thematic Progression theory explains textual meanings of how experiential and interpersonal meanings are organized in a linear and coherent way. Employing the rationale of T-P theory, this article analyses a lesson plan of teaching Explanation, and shows that T-P analysis can be employed in teaching writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…By employing Thematic Progression theory, Arunsirot's (2013) study reveals that there are five problems of theme found in students' writing which are the problem of empty theme, the problem of the brand new theme, the problem of overuse of constant progression, the problem of empty rheme, and the problem of confusing selection of textual theme. To improve students' writing skills, Thematic Progression analysis can be employed in teaching writing (Yang, 2008). Besides, textual theme and its types can be effectively applied in classrooms to help students in writings (Ebrahimi & Ebrahimi, 2012).…”
Section: Figurementioning
confidence: 99%
“…By employing Thematic Progression theory, Arunsirot's (2013) study reveals that there are five problems of theme found in students' writing which are the problem of empty theme, the problem of the brand new theme, the problem of overuse of constant progression, the problem of empty rheme, and the problem of confusing selection of textual theme. To improve students' writing skills, Thematic Progression analysis can be employed in teaching writing (Yang, 2008). Besides, textual theme and its types can be effectively applied in classrooms to help students in writings (Ebrahimi & Ebrahimi, 2012).…”
Section: Figurementioning
confidence: 99%
“…In the current literature, the first line of study into this aspect focuses on the analysis of TP in students' writing, some of which also investigate the correlation between TP and the marking (Ebrahimi & Khedri, 2012;Rakhman, 2013;Yang, 2015). Another field of interest is the instruction of TP for better application in writing, which has been carried out by Nurdianingsih and Purnama (2017), Purnomo (2014) and Yang (2008). Other studies also investigate the use of TP in other genres apart from students' writings, most commonly articles (Babaii et al, 2016;Jalilifar, 2010;Martıńez, 2003).…”
Section: Thematic Progression and Writing Performancementioning
confidence: 99%
“…According to (Maleki & Zangani, 2007), Students' writing cohesion can be supported by the use of theme and rheme in thematic progression patterns. Yang (2008) stated that thematic progression is very helpful in improving students' to organize text and it would help students improve their skills in writing. The theory of thematic progression focused on Theme and Rheme can be used to establish the flow of continuous knowledge to preserve the text's coherence and cohesion (Salzmann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%